If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5x+1)-6(18)=9(5x+3)
We simplify the equation to the form, which is simple to understand
2(5x+1)-6(18)=9(5x+3)
Reorder the terms in parentheses
+(+10x+2)-6*(18)=9*(5x+3)
Remove unnecessary parentheses
+10x+2-6+*(+18+)=+9+*(+5x+3+)
Reorder the terms in parentheses
+10x+2+(-108)=9*(5x+3)
Remove unnecessary parentheses
+10x+2-108=+9+*(+5x+3+)
Reorder the terms in parentheses
+10x+2-108=+(+45x+27)
Remove unnecessary parentheses
+10x+2-108=+45x+27
We move all terms containing x to the left and all other terms to the right.
+10x-45x=+27-2+108
We simplify left and right side of the equation.
-35x=+133
We divide both sides of the equation by -35 to get x.
x=-3.8
| 6a+2=20 | | m=10m+3 | | (0.15)=(3.2) | | 5t-1=6t | | 0.06x+0.045(1000-x)=93 | | 4x+6y+6=56 | | z-7=12 | | 7x+3x-(10x+12)=5+x | | 5z-7=12 | | 3x-(x-9)=2(x+5) | | 4x+6y=50 | | 6+y=19 | | 0.05y+0.10(5000-y)=0.20y | | 5/4(4x+2)=3 | | 7x+3x-(10x+12x)=5+x | | 5.0(2x-4)=-17 | | (17-m)3=12 | | -4x+-3x=5 | | 5x=4/5(5x-2) | | (5-f)6=-30 | | 7+n/2=10 | | 8x-3(4-2x)=6(y+1)-2 | | 36a^2-25d^2= | | 1/2(14x+2)=3(2-3x) | | P-(-2)=9 | | 10x+2y=12 | | 5x^3=6x^2 | | 5-4x=6+2 | | -3(n-10)= | | 2x+6=7x+21 | | log(4x-1)-log(x+2)=logx | | -1/4+f/8=1/2 |